TOXICOLOGICAL EVALUATION OF SUMITHION (OMS-43) ON OPERATORS AND INHABITANTS IN SOUTHERN IRAN - M.Motabar; GH.Sanai; AA. Heidari (Tehran University of Medical Sciences, 1973)
The aim of this trial was to determine the toxic effect of OMS-43 on spraymen and inhabitants. The spraying operation lasted for 30 successive days, and two teams consisting of 20 spraymen, 2 mixers, 4 foremen and team leaders were engaged in this operation. The operators were under systematic and closed clinical observation and cholinesterase determination (tintometric method) during the operation as well as, in some cases, two months after. In spite of the rigid instructions given to the spraymen to follow the necessary precautions, there were 42 cases of clinical symptoms. In some individuals several relapses occurred during the operation. No complaints or cholinesterase depression was observed during the first 2- week exposure. The main clinical symptoms were headache, giddiness, nausea and abdominal cramps; some workers felt weakness. Diarrhea was reported among two cases and was treated with Enterovioform (Ciba).A drop in whole blood CHE was seen among both mixers accompanied by clinical symptoms. One of the mixers left his job when his CHE was depressed to 12.5. Out of 20 spraymen, 8 showed depression of CHE in some cases with clinical symptoms. This study showed that the use of Sumithion under local conditions (sub- tropics, hot dry season) was safe for residents, but its toxic effect on operators should be considered and further toxicological investigations are requires under tropical conditions.